A narrative review on modern wound dressing for diabetes mellitus wound - Jamaludin, Sumaiyah @ ThandarSoe; Nurumal, Mohd. Said; Saidi, Sanisah; Che Hasan, Muhammad Kamil; Mohd Said, Nurezzatul Faseha; Samsudin, Nor Hafizah; Chong, Mei Chan (IIUM Press, 2020)
Introduction: Diabetic foot is a wide-ranging term for foot disorders includes infection, ulceration, or destruction of deep tissue due to peripheral neuropathy and ischemia from peripheral vascular disease. Wound dressings play a significant part in the treatment of diabetic foot ulcer (DFU). Modern wound dressing which is commonly known as the moist wound dressing can be better optional than the conservative one for the DFU. Aim: This study aimed to review the available articles on modern wound dressing for diabetes mellitus wound. Method: A total of six articles were reviewed and explained under the findings and discussion part of this study. The published articles from the year 2008 onwards are included in this narrative review. Result: Overall, it is evident that using of modern wound dressing can make sure excellent wound surroundings, avoid complications, improvement of quality of life of patients and aid the healing of DFU providing that the patient’s glycemic level is controlled. Conclusion: The process of wound healing in DFU is not static and it requires an appropriate environment at each stage of the healing process. And also a reasonable approach to the selection of dressing for certain types of wounds should be clarified. However, further study needs to be carried out to prove the current finding.